(3EYdGe GdfXGe GdYGdej GdLOjO (B:s (3GSJQGJjLjGJg heMOOGJg GdeYQajI JLGg GdefWbI GdYQHjI (B/s - (3GdYHSj, ESeGYjd YHO GdMGaXs ((3YeGf (B[(3GdCQOf(B] :s (3OGQ CeLO ddfTQ hGdJhRjY (B:s (3EHUGQ fGTQhf hehRYhf,s, 2020)
(3SjLO GdeJUaM dgPG GdcJGH Cf EYdGe GdfXGe GdYGdej gh EYdGe GdYhdeI, HebheGJgG GdeYQajI hGdKbGajI hGdEbJUGOjI hGdSjGSjI, hCf ESJQGJjLjJg JLGg GdefWbI GdYQHjI, JYHQ JYHjQG MQajG hehVhYjG Yf ESJQGJjLjI GdfXGe GdYGdej GdLOjO aj LhGfHgG GdSjGSjI hGdEbJUGOjI hGdLjhSJQGJjLjI JLGg gPg GdefWbI GdMjhjI ef GdYGde hGdeMOOI HJCejf MUhd GdhdGjGJ GdeJMOI hGdZQH Ydi GdfaW GdYQHj HSYQ ebHhd hGdMjdhdI Ohf hUhd Cj ef Gdbhi GdEbJUGOjI hGdYScQjI GdCNQi (B((3QhSjG, GdUjf(B)(3, Edi GdefWbI GdYQHjI heYGQVI bjGe eTQhYGJ bhejI, eKd GdhMOI GdYQHjI GdESdGejI(B.s
(3HHdjhLQGajI (B: (3UaMI (B181-192.s
Keywords: (3GdEYdGe GdOhdjs -- (3GdHdGO GdYQHjIs; (3GdEYdGe hGdSjGSI GdOhdjIs -- (3GdHdGO GdYQHjIs